Target Outcomes for Long-term Oral Health Care - Judith A. Jones, DDS, MPH; Elizabeth J. Brown, RDH, MS; Ladislav Volicer, MD, PhD (Blackwell Synergy, 2000)
This study developed a list of target outcomes for long-term oral health care in persons with dementia. A three-round Delphi study was used to develop a list of target outcomes. Participants included 99 staff and 171 family members associated with the Dementia Special Care Unit in Bedford, MA. In Round 1 participants were asked to list five outcomes for long-term oral health care. Items were grouped, redundancies removed, and fed back in Round 2, when participants scored the items from 1 (least important) to 10 (most important). Round 2 responses were tabulated and the top 20 were fed back for scoring in Round 3. The top 10 target outcomes in decreasing order of importance were: patient will be free from oral pain, patient will not be at risk for aspiration, emergency dental treatment will be available when needed, prevent mouth infections, daily mouth care is as much a part of daily care as shaving or brushing hair, prevent discomfort from loose teeth or sore gums, teeth will be brushed thoroughly once a day, staff will be able to provide oral hygiene care as needed, provide dental care to prevent problems eating, and recognize oral problems early.